Association between mortality and cardiovascular diseases in the vulnerable Mexican population: A cross-sectional retrospective study of the COVID-19 pandemic - Padilla-Rivas, Gerardo R.; Delgado-Gallegos, Juan Luis; Garza-Treviño, Gerardo; Galan-Huerta, Kame A.; G-Buentello, Zuca; Roacho-Pérez, Jorge A.; Santoyo-Suarez, Michelle Giovana; Franco-Villareal, Hector; Leyva-Lopez, Ahidée; Estrada-Rodriguez, Ana E.; Moreno-Cuevas, Jorge E.; Ramos-Jimenez, Javier; et al. (Frontiers in Public Health, 2022)
Cardiovascular diseases (CVDs) continue to be the leading cause of death worldwide. Over the past couple of years and with the surge of the COVID-19 pandemic, mortality from CVDs has been slightly overshadowed by those due to COVID-19, although it was during the peak of the pandemic. In the present study, patients with CVDs (CVDs; n = 41,883) were analyzed to determine which comorbidities had the largest impact on overall patient mortality due to their association with both diseases (n = 3,637). Obesity, hypertension, and diabetes worsen health in patients diagnosed positive for COVID-19. Hence, they were included in the overview of all patients with CVD. Our findings showed that 1,697 deaths were attributable to diabetes (p < 0.001) and 987 deaths to obesity (p < 0.001). Lastly, 2,499 deaths were attributable to hypertension (p < 0.001). Using logistic regression modeling, we found that diabetes (OR: 1.744, p < 0.001) and hypertension (OR: 2.179, p < 0.001) significantly affected the mortality rate of patients. Hence, having a CVD diagnosis, with hypertension and/or diabetes, seems to increase the likelihood of complications, leading to death in patients diagnosed positive for COVID-19.